Financial accountability of the homes of the orphans in the states of Johore and Malacca - Atan, Ruhaya; Mohd, Puzlah; Zainon, Saunah; Yaakob, Ahmad Nawawi (Penyelidikan, Pembangunan & Pengkomersilan, 2005)
Charities and voluntary organisations represent an increasingly important sector of the Malaysian economy. In 2003, there were about 96,579 non-profit organisations (NPOs) or non-governmental organisations (NGOs) registered with the Registry of Societies (ROS) in Malaysia. They were established to help the poor, orphans, religious causes, and others in need of social and charitable support. NPOs deal with huge resources from the public, donor agencies, and the government. They raise and utilise funds to work for various social issues. They play crucial roles in sustaining a vibrant and caring society, as well as promoting social reforms and protecting our well-being. Because of this, they need to operate effectively and maintain a high standard of accountability and transparency in their activities and financial matters. However, despite their economic and social importance, comparatively little attention has been paid to the provision of an adequate monitoring and control system, which would enable the performance of individual NPOs and charities to be effectively evaluated and inter-charity comparisons to be made. Concerns have been raised about the accountability of NPOs and charities, particularly the adequacy of current financial reporting and oversight mechanisms. Therefore, this study puts forward a proposal for an NPO model of accountability. In Malaysia, there is no regulatory framework or established Generally Accepted Accounting Practice (GAAP) for the charity sector. The only available information on NPOs that may be accessible to the public is the Annual Returns, excluding the financial statements. These returns can be obtained from the ROS for a fee. This study focuses on a selected type of NPO, namely orphanages in the states of Johor and Malacca. They are Pertubuhan Anak Yatim dan Miskin Sungai Udang, Malacca (PAYASUM) and Pertubuhan Kebajikan Anak-anak Yatim Islam (PICA YIS) Segamat, Johor. The functions of the Registry of Societies (ROS) in administering NPOs and enforcing the Societies Act 1966 are also included in this study. The study recommends that the Societies Act 1966 be reviewed to allow accessibility to financial statements; even if not publicly published, this would improve the transparency and accountability of NPOs. There should also be an oversight mechanism established by the government to ensure NPOs practise good governance.